Estratigrafia y estructura del devónico-carbonífero en el sector septentrional de la Sierra de la Punilla, precordillera de La Rioja y San Juan - Caminos, Roberto Luis (1993)
The stratigraphy and structure of the Devonian and Carboniferous units of northern Punilla rangeare analysed. The Punilla Formation mid-upper Devonian to lower Carboniferous in age, is the oldest unit recognized. It is composed by two sequences: the lower one is mainly sandstones with some conglomerate layers interbeded, the sandstones bear Malanzania antigua and Hyenia sp.. The upper sequence is characterized by a conglomerate-sandstone-shale association, in which several andesitic dykes were emplaced. Lower Carboniferous fossil plants Frenguellia eximia, Lepidodendropsis hirmeri, Diplothmema bodenbenderi, Eusphenopteris devonica and "Rodhea" (Archaeosigillaria- Lepidodendropsis Biozone) are present in this sequence. The Upper Carboniferous Quebrada Larga and Acerillos Formations are also described here as part of the inner Punilla range. Light gray and yellowish feldspatic sandstones, associated to swarm of andesitic dykes, characterize the first unit. These upper Carboniferous sediments are bearing Malanzania nana and Bothrychiopsis weissiana (NBG Biozone). An angular unconformity separate Quebrada Larga from Punilla Formation. The Acerillos Formation is a volcano- sedimentary complex, similar to the upper Carboniferous Punta del Agua Formation. The Devonian and Carboniferous units of La Punilla range are part of a folded arcuate belt, convex towards the west. The arc-shaped-belt is interpreted as a gondwanic structure originated by the deformation produced by a wedge of Umango basement rocks, which was controlled by two regional megafractures. The Punilla Formation folding is related to the intra-Carboniferous Rio Blanco tectonic phase.